Validation of the LUMIPULSE automated immunoassay for the measurement of core AD biomarkers in cerebrospinal fluid - Gobom, Johan; Parnetti, Lucilla; Rosa-Neto, Pedro; Vyhnalek, Martin; Gauthier, Serge; Cataldi, Samuela; Lerch, Ondřej; Laczo, Jan; Cechova, Katerina; Clarin, Marcus; Benet, Andrea L; Pascoal, Tharick A; et al. (Clinical chemistry and laboratory medicine, 2022)
OBJECTIVES: The core cerebrospinal fluid (CSF) biomarkers; total tau (tTau), phospho-tau (pTau), amyloid β 1-42 (Aβ 1-42), and the Aβ 1-42/Aβ 1-40 ratio have transformed Alzheimer's disease (AD) research and are today increasingly used in clinical routine laboratories as diagnostic tools. Fully automated immunoassay instruments with ready-to-use assay kits and calibrators has simplified their analysis and improved reproducibility of measurements. We evaluated the analytical performance of the fully automated immunoassay instrument LUMIPULSE G (Fujirebio) for measurement of the four core AD CSF biomarkers and determined cutpoints for AD diagnosis. METHODS: Comparison of the LUMIPULSE G assays was performed with the established INNOTEST ELISAs (Fujirebio) for hTau Ag, pTau 181, β-amyloid 1-42, and with V-PLEX Plus Aβ Peptide Panel 1 (6E10) (Meso Scale Discovery) for Aβ 1-42/Aβ 1-40, as well as with a LC-MS reference method for Aβ 1-42. Intra- and inter-laboratory reproducibility was evaluated for all assays. Clinical cutpoints for Aβ 1-42, tTau, and pTau was determined by analysis of three cohorts of clinically diagnosed patients, comprising 651 CSF samples. For the Aβ 1-42/Aβ 1-40 ratio, the cutpoint was determined by mixture model analysis of 2,782 CSF samples. RESULTS: The LUMIPULSE G assays showed strong correlation to all other immunoassays (r>0.93 for all assays). The repeatability (intra-laboratory) CVs ranged between 2.0 and 5.6%, with the highest variation observed for β-amyloid 1-40. The reproducibility (inter-laboratory) CVs ranged between 2.1 and 6.5%, with the highest variation observed for β-amyloid 1-42. The clinical cutpoints for AD were determined to be 409 ng/L for total tau, 50.2 ng/L for pTau 181, 526 ng/L for β-amyloid 1-42, and 0.072 for the Aβ 1-42/Aβ 1-40 ratio. CONCLUSIONS: Our results suggest that the LUMIPULSE G assays for the CSF AD biomarkers are fit for purpose in clinical laboratory practice. Further, they corroborate earlier presented reference limits for the biomarkers.
Keywords: peptidové fragmenty; proteiny tau; tau Proteins; Peptide Fragments; biologické markery; amyloidní beta-protein; Reproducibility of Results; lidé; Alzheimerova nemoc; reprodukovatelnost výsledků; Biomarkers; Alzheimer Disease; Humans; imunoanalýza; Amyloid beta-Peptides; Immunoassay